2011
DOI: 10.1177/0194599811427519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anatomy and Particle Size on Nasal Sprays and Nebulizers

Abstract: Objective To study the effects of nasal deformity on aerosol penetration past the nasal valve (NV) for varying particle sizes using sprays or nebulizers. Study Design Computed mathematical nasal airway model. Setting Department computer lab Subjects and Methods Particle deposition was analyzed using a computational fluid dynamics model of the human nose with leftward septal deviation and compensatory right inferior turbinate hypertrophy. Sprays were simulated for 10µm, 20µm, 50µm, or particle sizes follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 17 publications
(47 reference statements)
6
60
0
1
Order By: Relevance
“…(52) The choice of 1 m/s spray velocity was determined based on an earlier report by Frank et al (8) that showed higher nasal spray penetration at 1 m/s compared to 3 m/s and 10 m/s.…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…(52) The choice of 1 m/s spray velocity was determined based on an earlier report by Frank et al (8) that showed higher nasal spray penetration at 1 m/s compared to 3 m/s and 10 m/s.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…In particular, the presence of nasal anatomic deformities such as septal deviation has been reported to severely impede particle deposition. (6)(7)(8) Similarly, normal paranasal sinuses are usually altered by chronic rhinosinusitis, and management of this disease requires a combination of medical and surgical therapies. (31)(32)(33)(34)(35) Following sinus surgery, topical nasal drug medication is often prescribed to prevent recurrent disease.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of consistency in the literature on the number and type of grid elements required to provide numerically accurate CFD solutions for studies involving sinonasal insilico analysis of airflow and particulate matter, (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) even though most investigators performed airflow simulation using the finite volume method software package, FluentÔ (ANSYS, Inc., Canonsburg, PA). Among studies where mesh density analyses were reported, some authors failed to report details regarding how mesh refinement was done to achieve grid-independent numerical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…(8)(9)(10)(11)(12)18) In situations where particle transport was simulated (Table 1), the mesh structure utilized varied; some authors utilized unstructured tetrahedral meshes, (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)19,20) whereas other investigators used a hybrid of tetrahedral and prism meshes. (1)(2)(3)(14)(15)(16)(17)(18)21,22) The inclusion of prism boundary layers increases mesh density near airway walls and is generally considered to provide more accurate near-wall particle trajectory calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation